Role of cassava starch (Manihot esculenta Crantz) in reducing candida albicans adhesion on soft denture liners: an experimental study - Adena, Afif Surya; Naini, Amiyatun; Soesetijo, FX Ady; Kristiana, Dewi; Parnaadji, Rahardyan; Hardita, Ardhianing (Padjadjaran Journal of Dentistry, 2026)
Introduction: Soft denture liners can be an alternative solution for various removable denture problems, but they still have several limitations, such as promoting Candida albicans adhesion to dentures. Modifications incorporate cassava starch. The aim of this result is toanalyze the role of cassava starch in reducing Candida albicans adhesion on soft denture liners. Methods: This laboratory experimental study used twenty-seven disc-shaped heat-cured acrylic plates with a diameter of 10 mm and a thickness of 2 mm divided into three groups: acrylic plate without a coating (negative control group), acrylic plate coated with soft denture liners (positive control group), and acrylic plate coated with a soft denture liner containing cassava starch 15% (treatment group). The samples were soaked in artificial saliva for 1 hour, then contaminated with Candida albicans by placing them in a test tube containing a Candida albicans suspension, and incubated for 24 hours at 37°C. Samples were rinsed twice with PBS, then placed in a test tube containing 10 mL of Sabouraud's broth and vortexed for 30 seconds. The turbidity of the released Candida albicans was measured using a spectrophotometer. Absorbance data were analyzed using one-way ANOVA and post hoc LSD. Results: Turbidity testing using a spectrophotometer at 600 nm showed the average absorbance values were 0.013 for negative control group, 0.028 for the positive control group, and 0.019 treatment group. The results of the one-way ANOVA test showed a p-value of 0.004 (<0.05), indicating a significant difference between the groups. Further post hoc LSD tests showed that the positive control group had the highest absorbance value. At the same time, there was no significant difference between the negative control group and treatment group. Conclusion: Cassava starch inhibits Candida albicans adhesion to the soft denture liners.